Secondary metabolites from Mikania micrantha collected in the departament of Quindio and preliminary evaluation of the antimicrobial activity (Revista de Investigaciones Universidad del Quindío, 2013)
From the aerial parts of Mikania micrantha collected in Montenegro, Quindío (Colombia), were isolated the compounds: Acetyl-β-amyrin (1), Lupeol (2), Stigmasterol (3), Sesquiterpene lactones (SL) Mikanolide (4), Dihydromikanolide (5) Deoxymikanolide (6) and β-D-glucopyranoside of stigmasteryle (7). In order to compare the metabolic content, we studied a population collected in Paraíso-Guerrero (México), of the same species, obtaining the SL Xerantholide (8). Their structures were characterized by spectroscopic and chromatographic methods. Extracts and SL 4, 5 and 8 were tested against gram-positive bacteria (Staphylococcus aureus) and gram-negative (E. Coli, Pseudomona aeruginosa and Ralstonia solanacearum (race 2)). The results showed that the SL 8 percent inhibition was better than SL 4 and 5 against S. aureus and E. coli, while 4 exhibited a percentage of inhibition higher than 5 and 8 against Pseudomona aeruginosa.
Keywords: Mikania micrantha; Sesquiterpene lactones; Antimicrobial activity